Unlocking Students’ Enrolment: A Mixed Methods Study on How Brand Reputation and Perceived Benefits Shape Higher Education Choices in Tanzania - Magasi, Chacha; Bwemelo, Gordian Stanslaus (Universitas Djuanda, 2024)
As competition for student enrolment intensifies, higher education institutions must understand the factors influencing students' choices to ensure their sustainability and growth. The study investigated how brand reputation and perceived benefits affect higher education enrolment intention. The study employed a concurrent mixed-methods approach, combining quantitative data from surveys with qualitative data from Focus Group Discussions (FGDs) to comprehensively understand the research problem through a triangulation approach. The first objective involved conducting qualitative exploration through seven purposively selected focus group discussions (FGDs), applying thematic analysis to identify factors influencing enrolment choices. The second objective involved utilizing structured questionnaires to collect quantitative data from a representative sample of 119 randomly selected respondents. Multiple linear regression analysis was employed to analyze quantitative data and examine how brand reputation and perceived benefits influence enrolment intentions. The qualitative findings indicate that brand reputation, alum success, campus facilities, faculty expertise, financial aid, and academic programs are pivotal in shaping students' choices. Conversely, the quantitative analysis reveals that while brand names and compelling slogans positively affect enrolment intentions, brand logos do not yield a significant impact. These findings underscore the need for higher education institutions to prioritize brand reputation, alumni engagement, investment in campus facilities and faculty expertise, and financial support to enhance student attraction. This research extends brand equity theory to the higher education context, elucidating the significance of branding in enrolment decisions and enhancing academic discourse through its dual-method approach. The findings conclude that effective branding is a critical determinant of student enrolment choices, thereby offering substantial contributions to developing higher education marketing strategies.